2018
DOI: 10.1038/s41386-018-0241-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose intranasal oxytocin delivered with Breath Powered device modulates pupil diameter and amygdala activity: a randomized controlled pupillometry and fMRI study

Abstract: Little is known about how intranasally administered oxytocin reaches the brain and modulates social behavior and cognition. Pupil dilation is a sensitive index of attentional allocation and effort, and inter-individual variability in pupil diameter during performance of social-cognitive tasks may provide a better assessment of pharmacological effects on the brain than behavioral measures. Here, we leverage the close relationship between pupil and neural activity to inform our understanding of nose-to-brain oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 79 publications
2
25
2
Order By: Relevance
“…There is preliminary evidence for dose-dependent effects of oxytocin in both nonhuman 27,28 and human [29][30][31][32][33] species. This evidence was gathered in blood oxygen level-dependent (BOLD)-functional magnetic resonance imaging (fMRI) task-based studies, using paradigms that engage specific neural circuits, such as the amygdala, or measuring specific neurophysiological processes, such as pupil reactivity to emotional faces [29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is preliminary evidence for dose-dependent effects of oxytocin in both nonhuman 27,28 and human [29][30][31][32][33] species. This evidence was gathered in blood oxygen level-dependent (BOLD)-functional magnetic resonance imaging (fMRI) task-based studies, using paradigms that engage specific neural circuits, such as the amygdala, or measuring specific neurophysiological processes, such as pupil reactivity to emotional faces [29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…There is preliminary evidence for dose-dependent effects of oxytocin in both nonhuman 27,28 and human [29][30][31][32][33] species. This evidence was gathered in blood oxygen level-dependent (BOLD)-functional magnetic resonance imaging (fMRI) task-based studies, using paradigms that engage specific neural circuits, such as the amygdala, or measuring specific neurophysiological processes, such as pupil reactivity to emotional faces [29][30][31][32][33] . Overall, these studies indicated that lower-to-medium doses (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) of oxytocin may be more efficacious than higher doses, inspiring the current working hypothesis that the intranasal oxytocin dose-response curve follows an inverted-U shape 34 .…”
Section: Introductionmentioning
confidence: 99%
“…OT. 65 These results appear to suggest that OT can travel to the brain via a nose-to-brain route, as well as be transported from the systemic circulation after permeating the nasal mucosal membrane, which contains rich microvessel networks. Therefore, we considered the related question of whether the nasal routes are inhibited in RAGE KO (Ager -/-) male mice with respect to the extent that nasal-specific or via-blood routes can contribute to OT transport from the nasal cavity.…”
mentioning
confidence: 79%
“…This therapeutic option is appealing, given the relatively mild side effect profile of OT, and the ease of intranasal administration; however, the effect duration is relatively short. Substantial controversy remains about how and how much intranasally administered oxytocin reaches the brain in humans 67 , and the few human studies applying variable doses have yet to produce conclusive results 68 70 . The dose applied here (40IU) is the largest dose typically applied in human research.…”
Section: Discussionmentioning
confidence: 99%